PERTUMBUHAN EKONOMI, INDEKS PEMBANGUNAN MANUSIA DAN KEMISKINAN : BUKTI DARI PROVINSI BENGKULU - Tanjung, Ega Permana; Yuhendri L.V (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to investigate relationship economic growth and the human development index and poverty in Bengkulu Province between 2011 and 2021. Associative descriptive research techniques use secondary data from the Central Bureau of Statistics. The material breakdown employed Eviews 12 application is panel data regression analysis. The study's findings demonstrate how poverty in Bengkulu Province is both directly impacted. In the partial, poverty in Bengkulu Province is positively and insignificantly impacted by Economic Growth. Than, poverty in Bengkulu Province is negatively and significantly impacted by Human Development Index. In the simultaneously, poverty in Bengkulu Province is significantly impacted by both the economic growth and human development index.